A systematic review of interventions to enhance adherence and persistence with ADHD pharmacotherapy. (August 2022) - Parkin, Rebecca; Nicholas, Fiona Mc; Hayden, John C.
Abstract: Although high rates of poor adherence/persistence have been documented in ADHD, there is limited research targeting the problem. This systematic review evaluated interventions to address poor adherence/persistence to ADHD pharmacotherapy, with the aim of guiding the development of future interventions. An extensive search was conducted from January 1980 until January 2021. Thirteen studies were identified involving interventions based on psychoeducation, behavioural therapy, combined psychoeducation/behavioural therapy, technology-based interventions, written informed consent and a nursing support line. All 13 studies (including five RCTs) reported improvement in adherence/persistence and five studies (including four RCTs) also reported improvement in ADHD symptomatology. Almost all studies involved interventions utilising some form of education. Three RCTs of psychoeducation alone were included, with two of the three studies reporting adherence benefits at three and 12 months respectively. The third RCT was terminated early due to poor recruitment. A behavioural intervention RCT reported improved adherence six months post intervention (but not at 12 months), although a substantial drop-out rate was observed. A final included RCT used a Smartphone Application and reported a short term increase in adherence. The authors of the studies in this review make salient attempts at improving adherence and provide insight for future intervention development. We believe future interventions should involve combinations of strategies, have a theoretical framework and target the most common reasons for non-adherence. Interventions should also be integratable into routine care and include patient input to maximise sustainability.